Preparation method of array ultrahigh-temperature ceramic solid solution nanowire field emission cathode
The preparation of HfxTayC ultra-high temperature ceramic solid solution nanowires through chemical vapor deposition method solves the problem of high CNTs escape power, and realizes a high-performance field emission cathode, which has long-term stability and high beam brightness, which is suitable for extreme environments.
Patent Information
- Application Number
- CN202410756349.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-13
- Publication Date
- 2024-12-17
AI Technical Summary
In the prior art, carbon nanotubes (CNTs) have high egress function as field emitters, which limits their application as field emission cathode material. There are few reports on the field emission performance of HfxTayC ultra-high temperature ceramic solid solution nanowires.
Arrayed ultra-high temperature ceramic solid solution nanowires were prepared by chemical vapor deposition. By reacting the C/C composite matrix with HfCl4 and TaCl5 precursors at high temperature, HfxTayC ultra-high temperature ceramic solid solution nanowires were formed, with low work function and excellent High temperature stability and mechanical strength.
Achieve long-term current stability, high beam brightness, low energy diffusion and low operating vacuum, simplify the synthesis process, reduce equipment requirements, and have the potential of large-scale industrial production, broaden the field emission cathode materials at the extreme Application in the environment.
Smart Images

Figure CN119153288A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cathode field emission, and in particular relates to a method for preparing an arrayed ultra-high temperature ceramic solid solution nanowire field emission cathode. Background Art
[0002] There are four main types of electron emission: thermal emission, photoelectric emission, secondary electron emission, and field emission. In order to obtain a high-performance field emission cathode, the emission material can be made into a pointed cone shape to increase the field emission enhancement factor of the cathode, thereby establishing a strong electric field on the emission surface to obtain a high emission current. Field emission materials with relatively low work function or that are not easy to adsorb gas and are resistant to ion bombardment can also be selected to keep the work function and shape of the emitter stable, thereby obtaining a high stability and long-term cathode emission current. Therefore, one-dimensional nanomaterials, such as carbon nanotubes (CNTs), nanorods, nanocrystal chains, and nanowires, have become the focus of attention due to their unique geometric shapes.
[0003] CN112242281B reports a method for preparing CNTs as a field emitter, wherein a CNTs film is treated at a temperature of 1400-1800°C and a pressure of 40-60Mpa, and then a high-temperature heat treatment is performed to graphitize the CNTs structure, and one end of the CNTs structure is fixed between two adjacent electrode sheets to form a field emission preparation body, the field emission preparation body having an emission end, and the emission end of the field emission preparation body is bonded to form a CNTs field emitter for a field emission cathode material. CNTs are tens of microns or even hundreds of microns long, and have a large aspect ratio and a small radius of curvature, and can emit electrons under a relatively low excitation electric field, but the work function of CNTs is relatively high (about 4.55-5.05eV), which limits its application as a field emission cathode material.
[0004] Ultrahigh temperature carbide ceramics have low work function (ZrC: 3.60 eV, HfC: 3.40 eV), ultrahigh melting point, high mechanical strength and excellent physical and chemical stability, and are a promising field emission material. Reference 1 "Chiu TW, Tang J, Tang S, et al. Synthesis and field emission of ZrC nanowire. Materials Today Communications, 2020, 25: 101240." ZrC nanowires were prepared by CVD and their field emission properties were characterized. At a low extraction voltage of 555 V, 6.92×10 10 A / m 2Reference 2 "Tian S, Li HJ, Zhang YL, et al. Hafnium carbide nanocrystal chains for field emitters. Applied Surface Science, 2014, 305: 697-701." HfC nanocrystal chains were prepared by CVD method and further studies found that one-dimensional HfC has a low turn-on electric field (about 3.9 V / μm) and a high field enhancement factor (about 2157), showing good field emission performance.
[0005] Among the existing carbide ultra-high temperature ceramics, TaC has the same NaCl structure and similar crystallographic properties as HfC, which allows the Ta and Hf atoms in the TaC and HfC lattices to replace each other to form Hf x Ta y C solid solution. Hf x Ta y C solid solution has a higher melting point and better high temperature stability, can withstand high temperature environment caused by large emission current or thermal flash without degradation, has better mechanical strength and anti-ion sputtering ability, which is beneficial to the stability of emitter structure. x Ta y The field emission properties of C ultrahigh temperature ceramic solid solution nanowires have rarely been reported. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a technical solution: a method for preparing an arrayed ultra-high temperature ceramic solid solution nanowire field emission cathode, comprising the following preparation steps:
[0007] Step 1: Cut the size of 10×10×10mm 3 The surface of the C / C composite material substrate is polished, cleaned, dried, and then immersed in the catalyst solution for 0.5 to 5 hours;
[0008] Step 2: Take out the C / C composite material soaked in step 1, dry it in the shade, and then hang it in the high-temperature deposition area of the chemical vapor deposition furnace;
[0009] Step 3: Weighing an appropriate amount of refractory metal chloride precursor in a molar ratio and placing it in a powder feeding device for chemical vapor deposition of ultra-high temperature ceramic solid solution nanowires;
[0010] Step 4: Evacuate the deposition furnace to below 2KPa, check that it is airtight, introduce a protective gas at a flow rate of 100-500ml / min, and heat the deposition furnace to 1000-1400°C at a heating rate of 3-10°C / min;
[0011] Step 5: After the deposition furnace reaches the set temperature, introduce H2 and CH4, keep warm for 1 to 5 hours, turn off the heating program, stop introducing H2 and CH4, and wait for the deposition furnace to naturally cool to room temperature to obtain an ultra-high temperature ceramic solid solution nanowire field emission cathode.
[0012] The advantages of the present invention over the prior art are as follows: the present invention proposes an arrayed ultra-high temperature ceramic solid solution nanowire field emission cathode and a preparation method thereof, and prepares a new type of Hf by chemical vapor deposition. x Ta y C ultrahigh temperature ceramic solid solution nanowires. Studies have shown that this new type of electron source has excellent electron optical properties such as long-term current stability, high beam brightness, low energy diffusion, and low operating vacuum. This method has low requirements for equipment, simple synthesis process, fast synthesis rate, and large-area preparation, and has the potential for large-scale industrial production. In addition, arrayed Hf x Ta y The preparation of C ultrahigh temperature ceramic solid solution nanowires further broadens the application of field emission cathode materials in extreme environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 This is a schematic diagram of the field emission performance testing equipment of the present invention;
[0014] Figure 2 Preparation of Hf on C / C surface in Example 1 of the present invention x Ta y C Cross-sectional SEM images of ultrahigh temperature ceramic solid solution nanowires: (a) low magnification SEM image; (b) high magnification SEM image;
[0015] Figure 3 Preparation of Hf for Examples 1-3 of the present invention x Ta y The relationship between the emission current density and the applied electric field of the HfC and ZrC nanowires prepared as field emission cathodes by using ultra-high temperature ceramic solid solution nanowires and counter-examples 1-2, Figure 3 b is Figure 3 a Magnified image of the boxed area. DETAILED DESCRIPTION
[0016] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments.
[0017] Embodiment 1:
[0018] A method for preparing an arrayed ultra-high temperature ceramic solid solution nanowire field emission cathode comprises the following preparation steps:
[0019] Step 1: Cut the size of 10×10×10mm 3 The surface of the C / C composite material substrate was polished, cleaned, dried, and then immersed in an ethanol solution of nickel nitrate hexahydrate for 2 hours;
[0020] Step 2: Take out the C / C composite material soaked in step 1, dry it in the shade, and then hang it in the high-temperature deposition area of the chemical vapor deposition furnace;
[0021] Step 3: Weigh HfCl4 and TaCl5 precursors with a molar ratio of 1:3 and place them in a powder feeding device for chemical vapor deposition of ultra-high temperature ceramic solid solution nanowires;
[0022] Step 4: Evacuate the deposition furnace to below 2KPa, check that it is airtight, introduce a protective gas at a flow rate of 200ml / min, and heat the deposition furnace to 1100°C at a heating rate of 5°C / min;
[0023] Step 5: After the deposition furnace reaches the set temperature, H2 and CH4 are introduced at a flow rate of 300 ml / min and 100 ml / min respectively, and the protective gas flow rate is adjusted to 100 ml / min. After keeping warm for 2 hours, the heating program is turned off, and the introduction of H2 and CH4 is stopped. Wait for the deposition furnace to naturally drop to room temperature to obtain an ultra-high temperature ceramic solid solution nanowire field emission cathode.
[0024] Embodiment 2:
[0025] A method for preparing an arrayed ultra-high temperature ceramic solid solution nanowire field emission cathode comprises the following preparation steps:
[0026] Step 1: Cut the size of 10×10×10mm 3 The surface of the C / C composite material substrate was polished, cleaned, dried, and then immersed in an ethanol solution of nickel nitrate hexahydrate for 2 hours;
[0027] Step 2: Take out the C / C composite material soaked in step 1, dry it in the shade, and then hang it in the high-temperature deposition area of the chemical vapor deposition furnace;
[0028] Step 3: Weigh HfCl4 and TaCl5 precursors with a molar ratio of 1:1 and place them in a powder feeding device for chemical vapor deposition of ultra-high temperature ceramic solid solution nanowires;
[0029] Step 4: Evacuate the deposition furnace to below 2KPa, check that it is airtight, introduce a protective gas at a flow rate of 200ml / min, and heat the deposition furnace to 1150°C at a heating rate of 5°C / min;
[0030] Step 5: After the deposition furnace reaches the set temperature, H2 and CH4 are introduced at a flow rate of 300 ml / min and 100 ml / min respectively, and the protective gas flow rate is adjusted to 100 ml / min. After keeping warm for 2 hours, the heating program is turned off, and the introduction of H2 and CH4 is stopped. Wait for the deposition furnace to naturally drop to room temperature to obtain an ultra-high temperature ceramic solid solution nanowire field emission cathode.
[0031] Embodiment 3:
[0032] A method for preparing an arrayed ultra-high temperature ceramic solid solution nanowire field emission cathode comprises the following preparation steps:
[0033] Step 1: Cut the size of 10×10×10mm 3 The surface of the C / C composite material substrate was polished, cleaned, dried, and then immersed in an ethanol solution of nickel nitrate hexahydrate for 2 hours;
[0034] Step 2: Take out the C / C composite material soaked in step 1, dry it in the shade, and then hang it in the high-temperature deposition area of the chemical vapor deposition furnace;
[0035] Step 3: weighing HfCl4 and TaCl5 precursors with a molar ratio of 3:1 and placing them in a powder feeding device for chemical vapor deposition of ultra-high temperature ceramic solid solution nanowires;
[0036] Step 4: Evacuate the deposition furnace to below 2KPa, check that it is airtight, introduce protective gas at a flow rate of 200ml / min, and heat the deposition furnace to 1200°C at a heating rate of 5°C / min;
[0037] Step 5: After the deposition furnace reaches the set temperature, H2 and CH4 are introduced at a flow rate of 300 ml / min and 100 ml / min respectively, and the protective gas flow rate is adjusted to 100 ml / min. After keeping warm for 2 hours, the heating program is turned off, and the introduction of H2 and CH4 is stopped. Wait for the deposition furnace to naturally drop to room temperature to obtain an ultra-high temperature ceramic solid solution nanowire field emission cathode.
[0038] Comparative Example 1:
[0039] Step 1: Cut the size of 10×10×10mm 3 The surface of the C / C composite material substrate was polished, cleaned, dried, and then immersed in an ethanol solution of nickel nitrate hexahydrate for 2 hours;
[0040] Step 2: Take out the C / C composite material soaked in step 1, dry it in the shade, and then hang it in the high-temperature deposition area of the chemical vapor deposition furnace;
[0041] Step 3: Weigh the HfCl4 precursor and place it in a powder feeding device for chemical vapor deposition of HfC nanowires;
[0042] Step 4: Evacuate the deposition furnace to below 2KPa, check that it is airtight, introduce a protective gas at a flow rate of 200ml / min, and heat the deposition furnace to 1100°C at a heating rate of 5°C / min;
[0043] Step 5: After the deposition furnace reaches the set temperature, H2 and CH4 are introduced at a flow rate of 200 ml / min and 100 ml / min respectively, and the protective gas flow rate is adjusted to 100 ml / min. After keeping warm for 2 hours, the heating program is turned off, and the introduction of H2 and CH4 is stopped. Wait for the deposition furnace to naturally cool to room temperature to obtain the HfC nanowire field emission cathode.
[0044] Comparative Example 2:
[0045] A method for preparing an arrayed ultra-high temperature ceramic solid solution nanowire field emission cathode comprises the following preparation steps:
[0046] Step 1: Cut the size of 10×10×10mm 3 The surface of the C / C composite material substrate was polished, cleaned, dried, and then immersed in an ethanol solution of nickel nitrate hexahydrate for 2 hours;
[0047] Step 2: Take out the C / C composite material soaked in step 1, dry it in the shade, and then hang it in the high-temperature deposition area of the chemical vapor deposition furnace;
[0048] Step 3: Weigh the ZrCl4 precursor and place it in a powder feeding device for chemical vapor deposition of ZrC nanowires;
[0049] Step 4: Evacuate the deposition furnace to below 2KPa, check that it is airtight, introduce a protective gas at a flow rate of 200ml / min, and heat the deposition furnace to 1100°C at a heating rate of 5°C / min;
[0050] Step 5: After the deposition furnace reaches the set temperature, H2 and CH4 are introduced at a flow rate of 200 ml / min and 100 ml / min respectively, and the protective gas flow rate is adjusted to 100 ml / min. After keeping warm for 2 hours, the heating program is turned off, and the introduction of H2 and CH4 is stopped. Wait for the deposition furnace to naturally cool to room temperature to obtain the ZrC field emission cathode.
[0051] Figure 1 This is the principle diagram of the field emission performance testing equipment of the present invention. Figure 2 The SEM cross-sectional image of the test sample shows that the thickness of the C / C surface nanowire layer is ∼80 μm ( Figure 2 a), the nanowires grow perpendicular to the C / C substrate surface and present an array distribution ( Figure 2 b). Figure 3 Preparation of Hf for Examples 1-3 of the present invention x Ta yThe relationship between the emission current density and the applied electric field of the HfC and ZrC nanowires prepared as field emission cathodes using ultrahigh temperature ceramic solid solution nanowires and counterexamples 1-2 is shown in Figure 1. It can be seen that the field emission current density increases almost exponentially with the increase of the electric field. When the current density reaches 10 μA cm -2 When Hf x Ta y The applied electric field of C ultrahigh temperature ceramic solid solution nanowires is lower than that of ZrC and HfC. It is worth noting that the Hf 0.5 Ta 0.5 The applied electric field of C ultrahigh temperature ceramic solid solution nanowires after heat treatment at 1700℃ is also lower than that of ZrC and HfC, indicating that Hf x Ta y C ultrahigh temperature ceramic solid solution nanowires have excellent high temperature stability.
[0052] The present invention and its implementation methods are described above, and such description is not restrictive. In short, if a person skilled in the art is inspired by it and, without departing from the purpose of the invention, designs structures and embodiments similar to the technical solution without creativity, they should all fall within the protection scope of the present invention.
Claims
1. A method for preparing an arrayed ultra-high temperature ceramic solid solution nanowire field emission cathode, characterized in that: The method comprises the following preparation steps: Step 1: Cut the size of 10×10×10mm 3 The surface of the C / C composite material substrate is polished, cleaned, dried, and then immersed in the catalyst solution for 0.5 to 5 hours; Step 2: Take out the C / C composite material soaked in step 1, dry it in the shade, and then hang it in the high-temperature deposition area of the chemical vapor deposition furnace; Step 3: Weighing an appropriate amount of refractory metal chloride precursor in a molar ratio and placing it in a powder feeding device for chemical vapor deposition of ultra-high temperature ceramic solid solution nanowires; Step 4: Evacuate the deposition furnace to below 2KPa, check that it is airtight, introduce a protective gas at a flow rate of 100-500ml / min, and heat the deposition furnace to 1000-1400°C at a heating rate of 3-10°C / min; Step 5: After the deposition furnace reaches the set temperature, introduce H2 and CH4, keep warm for 1 to 5 hours, turn off the heating program, stop introducing H2 and CH4, and wait for the deposition furnace to naturally cool to room temperature to obtain an ultra-high temperature ceramic solid solution nanowire field emission cathode.
2. The method for preparing an arrayed ultra-high temperature ceramic solid solution nanowire field emission cathode according to claim 1, characterized in that: In step 1, the substrate is a conductive carbon material substrate, including but not limited to: one of C / C composite materials, graphite, and carbon cloth.
3. The method for preparing an arrayed ultra-high temperature ceramic solid solution nanowire field emission cathode according to claim 1, characterized in that: In step 1, the catalyst solution includes ethanol or aqueous solution of Ni metal salt.
4. The method for preparing an arrayed ultra-high temperature ceramic solid solution nanowire field emission cathode according to claim 1, characterized in that: In step 2, the precursor powder is a refractory metal chloride, including but not limited to: one of HfCl4 and TaCl5.
5. The method for preparing an arrayed ultra-high temperature ceramic solid solution nanowire field emission cathode according to claim 1, characterized in that: In step 3, the ultra-high temperature ceramic solid solution nanowires are HfxTayC, and 0≤x≤1, 0≤y≤1.
6. The method for preparing an arrayed ultra-high temperature ceramic solid solution nanowire field emission cathode according to claim 1, characterized in that: In step 4, the protective gas includes but is not limited to one of Ar and N2.
7. The method for preparing an arrayed ultra-high temperature ceramic solid solution nanowire field emission cathode according to claim 1, characterized in that: In step 5, the H2 flow rate is 200-400 ml / min, the CH4 flow rate is 50-100 ml / min, and the protective gas flow rate is 50-200 ml / min.
